Considerations for Patients With Peripheral Artery Disease During the COVID-19 Pandemic. (29th March 2021) - Farhan, Serdar; Kamran, Haroon; Vogel, Birgit; Garg, Karan; Rao, Ajit; Narula, Navneet; Jacobowitz, Glenn; Tarricone, Arthur; Kapur, Vishal; Faries, Peter; Marin, Michael; Narula, Jagat; et al.
New York City was one of the epicenters of the COVID-19 pandemic. The management of peripheral artery disease (PAD) during this time has been a major challenge for health care systems and medical personnel. This document is based on the experiences of experts from various medical fields involved in the treatment of patients with PAD practicing in hospitals across New York City during the outbreak. The recommendations are based on certain aspects including the COVID-19 infection status as well as the clinical PAD presentation of the patient. Our case-based algorithm aims at guiding the treatment of patients with PAD during the pandemic in a safe and efficient way.